Outcome of Phacoemulsification and Extracapsular Cataract Extraction - Fawad Ahmad, Mohammad Aamir Khan, Shahid Nazeer, Zubair Ullah Khan, Muhammad Usman Arshad, Sohail Zia (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Aim was to compare the visual results of patients who received ECCE and phacoemulsification for the treatment of age-related cataracts. Study Design: Prospective study Place and Duration: Conducted at Jinnah International Hospital during from Jan, 2021 to Dec, 2021. Methods:There were 130 patients of both genders presented for cataract surgery. Patients were aged between 35-75 years.When patients signed an informed permission form, demographic information such as age and sex were recorded. Patients were equally divided in two groups. Group I received phacoemulsification (phaco) cataract surgery and group II received conventional extracapsular cataract extraction. Intraoperative and post-operative complication among cases was assessed. At last follow up best corrected visual acuity was assessed and compared among both groups. SPSS 24.0 was used to analyze complete data. Results:Among 130 cases, majority of the cases 85 (65.4%) were males and 45 (34.6%) were females. 15 (11.5%) patients were aged between 35-45 years, 45 (34.6%) patients were aged between 46-55 years, 38 (29.2%) were aged between 56-6 years and 32 (24.6%) had age > 65years. Post-operative we found significantly good vision among patients of phaco group in 54 (83.1%) cases as compare to group II in 31 (47.7%) cases. Frequency of intraoperative complications was higher in group II 9 (13.8%) as compared to group I 3 (4.6%) cases. Post-operative complications in group I was corneal decompensation, high astigmatism and posterior capsule opacity but in group II high astigmatism and corneal decompensation were the complications. Conclusion:We came to the conclusion that the visual outcome was considerably better in the Phaco operation compared to the ECCE technique (p = 0.003). As a result, we advocate for the provision of Phaco equipment in hospitals that have sufficient capabilities for the performance of intraocular surgery.